Cultural safety and the challenges of translating critically oriented knowledge in practice - Browne, Annette J. (Nursing philosophy, 2009)
Cultural safety is a relatively new concept that has emerged in the New Zealand nursing context and is being taken up in various ways in Canadian health care discourses. Our research team has been exploring the relevance of cultural safety in the Canadian context, most recently in relation to a knowledge-translation study conducted with nurses practising in a large tertiary hospital. We were drawn to using cultural safety because we conceptualized it as being compatible with critical theoretical perspectives that foster a focus on power imbalances and inequitable social relationships in health care; the interrelated problems of culturalism and racialization; and a commitment to social justice as central to the social mandate of nursing. Engaging in this knowledge-translation study has provided new perspectives on the complexities, ambiguities and tensions that need to be considered when using the concept of cultural safety to draw attention to racialization, culturalism, and health and health care inequities. The philosophic analysis discussed in this paper represents an epistemological grounding for the concept of cultural safety that links directly to particular moral ends with social justice implications. Although cultural safety is a concept that we have firmly positioned within the paradigm of critical inquiry, ambiguities associated with the notions of ‘culture’, ‘safety’, and ‘cultural safety’ need to be anticipated and addressed if they are to be effectively used to draw attention to critical social justice issues in practice settings. Using cultural safety in practice settings to draw attention to and prompt critical reflection on politicized knowledge, therefore, brings an added layer of complexity. To address these complexities, we propose that what may be required to effectively use cultural safety in the knowledge-translation process is a ‘social justice curriculum for practice’ that would foster a philosophical stance of critical inquiry at both the individual and institutional levels.